Job assignments under moral hazard: the Peter Principle revisited - Alexander K. Koch; Julia Nafziger (Institute for the Study of Labor (IZA), 2007)
The Peter Principle captures two stylized facts about hierarchies: first, promotions often place employees into jobs for which they are less well suited than for that previously held. Second, demotions are extremely rare. Why do organizations not correct 'wrong' promotion decision? This paper shows in a complete contracting setting that a simple trade-off between incentive provision and efficient job assignment may make it optimal to promote some employees to a job at which they produce less than they would at the previous level.
Keywords: 330; Erwerbsverlauf; Anforderungsprofil; Moral Hazard; Leistungsanreiz; Theorie